TINJU ADAT DESA LEGUDERU KECAMATAN BOAWAE KABUPATEN NAGEKEO - Eusabius Ferceli So'o Kowe; Fransiskus Mario Charlos (Pineleng Theological Review, 2025)
This article discusses Etu, a traditional boxing ritual practiced by the Boawae community in Nagekeo Regency, within the broader context of cultural preservation and ritual expression in Indonesia. More than just a physical contest, Etu serves as a thanksgiving ceremony for harvests and embodies values of gratitude, communal unity, and sacred tradition. The study aims to explore the symbolic meanings and cultural functions of Etu amid the changing realities of modern life and migration. Using a qualitative, narrative-descriptive approach, data were collected through semi-structured interviews and literature review. Findings show that Etu is governed by customary rules, involves symbolic attire, sacred spaces, and distinct roles. While the ritual remains vibrant in its local setting, diaspora communities face challenges in practicing it due to limited resources and the absence of traditional structures. Nevertheless, the study identifies potential strategies for cultural preservation through digital means, such as live streaming and virtual participation. villages and those who have migrated elsewhere.